The EU Charter as a Catalyst for Environmental Action: Spotlighting Articles 37 and 47 - Vomáčka, Vojtěch (Human Rights and Environmental Protection from a Central and Eastern European Perspective, 2026)
The Charter of Fundamental Rights of the European Union has emerged as a powerful instrument for environmental protection within the bloc. This chapter delves into the Charter’s relevance in this domain, analysing its impact beyond mere legal pronouncements. It explores how the Charter elevates environmental considerations to a core principle within the EU (Article 37), empowering individuals and organisations to champion a healthy planet (Article 47). The chapter examines how the Charter’s emphasis on continuous improvement drives the development of ambitious environmental goals and fosters a legal landscape where environmental protection remains a top priority. It further analyses the Charter’s interplay with existing EU environmental legislation, highlighting its role in ensuring a robust and unified approach to environmental safeguards. Finally, the relationship between the EU Charter and the European Convention on Human Rights (ECHR) is considered, exploring both convergence and divergence in their approaches to environmental protection and fair trial rights.